Knowledge Integration Among Flood Disaster Management Team: Lessons from The Kemaman District - Zakaria, Nor Hidayati; Ahmad, Mohammad Nazir; Mohd Noor, Mohd Saiful Anuar; Ahmad, Mazida (Universiti Utara Malaysia Press, 2018)
Although flooding is a common disaster event in Malaysia, issues such as information and knowledge integration still have yet to be resolved. Flood management operations seem to be handled in an ad-hoc manner comprising issues such as miscommunication, lack of common understanding during coordination practices, and lack of smooth mutual agreement among flood management agencies. Thus, this paper discusses the flood knowledge integration measures that have been applied by the flood management team for Kemaman District, Terengganu, the first district achieved a Gold Standard award for flood disaster management in Malaysia. This study comprises a qualitative research method using a variety of techniques. These include a case study approach performed by interviewing key informants as well as studying archival documents. In addition, site visits were made to flood location areas in order to better understand the districts flood management team's achievement. The result of knowledge integration practice in preliminary, actual and post-flood phases is discussed in this research. This study shows the importance of knowledge integration as a successful factor for the districts flood management plan.